Peradaban Islam di Indonesia - Ismail Pane (Indra institute Research & Publication, 2023)
Islam in Indonesia as a religion with the most adherents has its own uniqueness in the history of its development. Indonesian Islam is propagated, taught and adhered to peacefully and without coercion. There are several theories about the history of the arrival of Islam in Indonesia.The diversity of theories is caused by the phenomenon of complexity, namely Islam does not originate from one place/country, nor is it brought by one group of people and not all at once Islam was developed by Ulama through three channels namely; cultural (da'wah, education, art, culture, and marriage), structural (politics and power), economy (trade routes). In other words, the process of Islamization in Indonesia is influenced by political power and the spirit of preaching.